Identifying the pedoclimatic conditions most critical in the susceptibility of a grapevine cultivar to esca disease - Valérie Hofstetter; Vinciane Monod; Matthieu Wilhelm; Olivier Viret; Katia Gindro; Daniel Croll; Vivian Zufferey (OENO One)
Esca, one of the most destructive grapevine trunk diseases, is still poorly understood. As grapevine cultivars vary widely in their susceptibility to esca, we designed a four-year experiment to identify the environmental factors that influence the expression of the disease in a susceptible cultivar. We collected epidemiological and physiological data once a year for four consecutive years in 19 vineyard plots located in four wine-growing regions of Western Switzerland. We compared these data with climatic data obtained from weather stations for these same plots for four years and over the long term. We also estimated the soil water holding capacity of each plot. Confounding factors were minimal because all vineyards were planted in 2003 with the same cultivar and all plants grafted in the same nursery with genetically homogeneous grafting material. Principal component and regression analyses of combined epidemiological, biotic and pedoclimatic data identified a positive correlation between soil water retention capacity and plant mortality due to esca. These analyses also showed that leaf disease symptoms and apoplexy are more frequent when cold and wet periods are followed–or alternate with–hot and dry periods, and that apoplexy occurs more frequently when weather conditions change abruptly (a cold and wet May followed by a hot June) and deviate significantly from long-term climatic conditions. Regression analyses show that the soil water holding capacity impacts less the disease expression when the climate is warm and dry, both at the regional and year-specific levels. Having identified the most important environmental factors towards the expression of esca, this study allows recommendations to be given to the winegrowers for the cultivar studied but can also be used as a model to identify the environmental factors that influence the expression of fungal diseases in other grapevine cultivars and other grapevine trunk diseases.